Embedded low-power environment monitoring tool for remote water quality monitoring (Journal on studies and research of academic knowledge, 2021)
Water is an essential factor for living beings, on which the quality of life depends. At present, population growth and the increase in pollutants in the environment lead to the deterioration of water channels. Therefore, their constant monitoring for remediation or early action is increasingly important. Under these considerations, this research has developed a device (sensor node) of reduced size (~ 5 x 5 cm) equipped with a considerable number of sensors (up to seven) primarily for monitoring water. The resulting system, implemented on a printed circuit board, offers flexibility for data transmission and storage while being energy efficient (
Keywords: pH; Turbidity; TDS; Energy Harvesting; Wireless